Design and optical study of a microwave plasma torch in nitrogen used for the evaporation of aluminium wires. Issue 5 (28th November 2017) - Pipa, A.V.; Sushentsev, D.; Hamann, S.; Dufloux, C.; Ionikh, Yu.Z.; Hannemann, M.; Wiese, M.; Röpcke, J.; Wollweber, J.
Abstract : A microwave torch in nitrogen has been designed for the evaporation of aluminium (Al) wires potentially to be used for the synthesis of aluminium nitride (AlN). The torch, created on the tip of a metallic nozzle, is compatible with vacuum conditions and can be operated in continuous mode up to atmospheric pressure. Al wires to be evaporated are fed through the axis of the nozzle. Time‐resolved photography is applied to analyse the time evolution and stability of the interaction of the Al wire with the discharge. Optical emission spectroscopy is used (a) for the determination of the gas temperature of the active discharge, which is found to be in the range 1500–3500 K depending on the experimental conditions, and (b) for the estimation of the densities of Al and N atoms in the afterglow region, which are in the range 10 11 –10 12 and of 10 13 –10 14  cm −3, respectively. It is found that the part of the Al wire that is directly exposed to the nitrogen torch absorbs a considerable amount of the microwave energy, supporting its evaporation. In addition, the dissociation of molecular nitrogen has to be considered as an important process of power dissipation. Further technical development of the torch is necessary for the envisaged synthesis of AlN.